A study on the effectiveness of promotion forms implemented by Pusat Zakat Melaka (PZM) towards Muslim government employees / Mohd Azri Md Yatim - Md Yatim, Mohd Azri (Faculty of Business and Management, 2010)
This study will examine the motive to determine the effectiveness of promotional tools that implement by Pusat Zakat Melaka (PZM) towards Muslim government employees in Melaka to pay zakah on employment income; and to examine the best promotional tools that can enhance on Muslim employees in government sector in Melaka to pay zakah on employment income. At the same time, the study needs to examine the level of compliance towards paying zakah on employment income among government sector in Melaka. Few independent variables are taken to test whether there are any significant correlation between the dependent and independent variables.